Preparation of shape-stabilized phase change material nanocomposite using palm kernel shell activated carbon for thermal energy storage - Nicholas, Ahmad Fariz (2019)
Nanomaterials study is an emerging field of research that received considerable attention due to their potential impact on every domain of science and technology. Their benefits to the various fields of study in research and application such as waste water treatment, biomedical, electronics and energy storage makes nanomaterials broad and interdisciplinary in research and development. The constant growth of increase in waste materials and need for energy caused serious international concern towards the biodiversity. This issue can be matched with thermal energy storage (TES) which is the temporary storage of high or low temperature energy from direct solar energy. TES in buildings has recently attracted much attention. The applications of phase change material (PCM) as the medium for energy storage in the buildings were designated as to reduce and maintained the comfort temperature. Activated carbon as the framework materials for PCM have the potential to protect the PCM from the external environment, increase the heat transfer area, control the volume changes and increase the thermal conductivity during the application. The aim of this study is to prepare shape-stabilized phase change material (SSPCM) for TES application in the building. Palm kernel shell (PKS) was used as the precursor and treated with H3PO4 at different concentration and activated at different temperatures in different holding time for the optimization as to see the effect towards the physico-chemical properties of the activated carbon. The effect of surface area of palm kernel shell activated carbon (PKSAC) framework towards the PCM also studied by the impregnation of the n-octadecane into different surface area of the activated carbon treated with different H3PO4 concentration. The result shows that the PKSAC treated with 20% H3PO4 gave the highest value of 1169 m2g-1 and average pore size of 27 Å. In general, this study shows the best activation temperature, holding time and treatment of H3PO4 in the preparation of PKSAC was 500 oC, 2 h and 20% H3PO4 respectively. In addition, the specific surface area plays a crucial role towards the properties of the resulting SSPCM prepared.